Sustainable Recycling Technology for Li-Ion Batteries and Beyond: Challenges and Future Prospects - Fan, Ersha; Li, Li; Wang, Zhenpo; Lin, Jiao; Huang, Yongxin; Yao, Ying; Chen, Renjie; Wu, Feng (Chemical reviews, 2020)
Tremendous efforts are being made to develop electrode materials, electrolytes, and separators for energy storage devices to meet the needs of emerging technologies such as electric vehicles, decarbonized electricity, and electrochemical energy storage. However, the sustainability concerns of lithium-ion batteries (LIBs) and next-generation rechargeable batteries have received little attention. Recycling plays an important role in the overall sustainability of future batteries and is affected by battery attributes including environmental hazards and the value of their constituent resources. Therefore, recycling should be considered when developing battery systems. Herein, we provide a systematic overview of rechargeable battery sustainability. With a particular focus on electric vehicles, we analyze the market competitiveness of batteries in terms of economy, environment, and policy. Considering the large volumes of batteries soon to be retired, we comprehensively evaluate battery utilization and recycling from the perspectives of economic feasibility, environmental impact, technology, and safety. Battery sustainability is discussed with respect to life-cycle assessment and analyzed from the perspectives of strategic resources and economic demand. Finally, we propose a 4H strategy for battery recycling with the aims of high efficiency, high economic return, high environmental benefit, and high safety. New challenges and future prospects for battery sustainability are also highlighted.